Impact of Distributed Photovoltaic Generation on Relay in Distribution Network - ZHAI Wenjie; LI Jianquan; WU Xiaoyun; GUAN Rende; CUI Jian (Kongzhi Yu Xinxi Jishu)
Sensitivity and selectivity of relay protection are influenced by distribution network grid-connected distributed photovoltaic generation. Therefore, a protective approach was studied in response to this problem and then a theoretical analysis method was provided for increasing or reducing fault current under different situations. Based on radial distribution network and constant impedance load model, taking distributed photovoltaic generation as a controlled current source, the impact of fault current of distributed photovoltaic generation on distribution network was simulated and then the correctness of the theoretical analysis was verified.